Determinants of green finance implementation in Indonesia: Evidence from panel data analysis of institutional, market, issuer, and macroeconomic factors - Simanullang, Fransiska; Simanullang, Sairun (Priviet Social Sciences Journal, 2025)
Green finance has emerged as a critical mechanism for mobilizing capital toward climate change mitigation and sustainable development, particularly in emerging economies. This study investigates the determinants of green finance implementation in Indonesia, focusing on five key drivers: macroeconomic conditions, issuer characteristics, governance effectiveness, financial market development with big data capabilities, and policy and regulatory support. Using a balanced panel dataset of twenty-five issuers and projects over forty quarterly periods from 2015 to 2024, and employing a fixed effects panel regression in EViews, the analysis reveals that governance effectiveness and policy and regulatory support exert the strongest positive influence on green finance implementation. Financial market depth and technological readiness, as well as favorable issuer-level structures, also contribute positively, whereas adverse macroeconomic conditions are associated with reduced uptake of green instruments. The model explains over 76% of the variation in green finance implementation, underscoring the multidimensional nature of sustainable finance in Indonesia. The findings highlight that institutional credibility, coherent policy frameworks, market infrastructure, and issuer capacity-building are essential for accelerating the scale and effectiveness of green finance. Policy implications include strengthening governance systems, enhancing ESG data infrastructure, and ensuring macroeconomic stability to foster a resilient and attractive green finance ecosystem.